Effect Of Recycled Carbon Fiber Reinforcement On The Wear Behavior Of Epoxy Composite - Qumrul, Ahsan; Law, Mei Lin; Rose Farahiyan, Munawar; Noraiham, Mohamad (Cambridge University Press, 2016)
In the recent years, carbon fiber reinforced polymer (CFRP) composites have formed a very important class of tribo-engineering materials in nonlubricated condition. The usage of CFRPs has been growing at a substantial rate that leads to the increasing amount of waste generated from end-of-life components and manufacturing scrap. In the present paper, the role of as-received (rCF-AR) and cryogenic treated (rCF-T) recycled carbon fiber (rCF) reinforcements were investigated on the tribological behavior of epoxy composites by using a micro pin-on-disc tribotester apparatus under dry sliding condition. The wear behavior of the composites was analyzed based on three different sliding velocities and loads at a constant sliding distance. The results showed that the reinforcement effect of rCF-T as compared to rCF-AR has enhanced the wear resistance of epoxy composite, which is attributed to the improved adhesion between the treated rCFs and epoxy matrix.